The teaching of health geography: A way of thinking about the dynamics of the territory to promote health in schools (Revista Contexto & Educação, 2023)
The present work aims to emphasize the importance of the Health Geography teaching practices in schools. In order to do so, a documentary analysis was carried out where the main material used was the Health and Environmental Education Notebook (2015), associated to the Health at School Program, which proposes a systemic view between the social determinants of health and the territory. Based on this, health geography teaching practices were formulated to be used by teachers in their classes, as well as a fieldwork proposal that aims to bring students closer to the used territory in order to promote awareness to the health issues and encourage autonomy so that they can act in the search for healthier spaces. Through this, we understand that the teaching of Health Geography has a great potential to promote health in schools, since it teaches students to act preventively on the social determinants of health, improving personal and collective care, which decreases the risk of spreading diseases and can improve the population's welfare levels.